Pengaruh Program Latihan Pliometrik Terhadap Peningkatan Power Tungkai pada Atlet Lompat Jauh - Muhammad Jabbar Balya; Agus Gumilar; Ahmad Hamidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Leg power is one of the biomotor components that greatly determines the success of long jump athletes, especially in the take-off phase. One of the most widely used training methods to increase leg muscle explosive power is plyometric training, which utilizes the stretch-shortening cycle (SSC) mechanism. However, research on the effectiveness of plyometric training in adolescent long jump athletes in Indonesia remains limited. This study aims to determine the effect of a plyometric training program on increasing leg power in adolescent long jump athletes and to analyze the effect size of the program. The study used a quantitative approach with a One Group Pretest-Posttest Design. The research sample consisted of 10 adolescent long jump athletes selected using a total sampling technique. Leg power was measured using the 30-Second Sit-to-Stand (30s STS) test before and after the plyometric training program. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Paired Samples t-test, and Cohen's d calculation to measure effect size at a significance level of 5%. The results showed: (1) the average pretest score was 49.40, while the average posttest score increased to 54.90, with an average increase of 5.50 points; (2) the normality test showed that the pretest (Sig. = 0.953) and posttest (Sig. = 0.999) data were normally distributed; (3) the Paired Samples t-test showed a significance value of p < 0.001, indicating a significant difference between the pretest and posttest scores; (4) the Cohen's d analysis yielded a value of 2.09, indicating that the plyometric training program had a huge positive effect on increasing athletes' leg power. It can therefore be concluded that the plyometric training program is effective and has a significant effect on increasing leg power in adolescent long jump athletes. Keywords: Effect Size, Plyometric Training, Long Jump, Leg Power, Stretch-Shortening Cycle